Repeated low-intensity noise exposure exacerbates age-related hearing loss via RAGE signaling pathway - Jianbin Sun; Na Sai; Tong Zhang; Chaoying Tang; Shuhang Fan; Qin Wang; Da Liu; Xianhai Zeng; Juanjuan Li; Weiwei Guo; Shiming Yang; Weiju Han (Neurobiology of Disease)
Repeated low-intensity noise exposure is prevalent in industrialized societies. It has long been considered risk-free until recent evidence suggests that the temporary threshold shift (TTS) induced by such exposure might be a high-risk factor for hearing loss. This study was conducted to further investigate the manner in which repeated low-intensity noise exposure contributed to hearing damage. Two-month-old C57BL/6 J mice were exposed to white noise at 96 dB SPL for 8 h per day over 7 days to induce TTS. Auditory brainstem response (ABR) was monitored to assess changes in hearing thresholds, tracking the effects of noise exposure until the mice reached 12 months of age. Our results indicated that noise-exposed mice exhibited accelerated age-related hearing loss spanning from high to low frequencies. Proteomics analysis revealed an upregulation in the receptor for the advanced glycation end-products (RAGE) signaling pathway, which was associated with an activated inflammatory response, vascular injury, and mitochondrial and synaptic dysfunction. Further analysis confirmed increased levels of inflammatory cytokines in the cochlear lymph fluid and significant macrophages infiltration in the cochlear lateral wall, accompanied by hyperpermeability of the blood-labyrinth barrier. Additionally, degenerated mitochondria in the outer hair cells and decreased synaptic ribbons in the inner hair cells were also observed. These pathological changes indicated that noise exposure damages the cochlear cellular components, increasing the cochlear susceptibility to age-related stress. Our findings suggest that TTS caused by repeated low-intensity noise exposure correlates with a severe sensorineural hearing loss during aging; targeting the RAGE signaling pathway may be a promising strategy to mitigate damage from low-intensity noise and slow down the progression of age-related hearing loss.